On the taxonomy of the genus Thyridanthrax Osten Sacken in Egypt and the Kingdom of Saudi Arabia, with description of a new species (Diptera: Bombyliidae) - El-Hawagry, Magdi S.; Abdel-Dayem, Mahmoud S.; Dhafer, Hathal M. Al (Zootaxa, 2019)
Egyptian and Saudi Arabian Thyridanthrax spp. collected in field trips or preserved in the Efflatoun’s insect collection in Cairo University were taxonomically studied. One new species, T. elegansoides sp. nov., is herein described, and two species, T. decipulus (Austen) and T. polyphemus (Wiedemann), are newly recorded from Egypt. Ten species are treated: one species from the Kingdom of Saudi Arabia, T. anomalus Greathead; two species from Egypt and the Kingdom of Saudi Arabia, T. decipulus (Austen) and T. perspicillaris (Loew); and seven species from Egypt: T. elegans (Wiedemann), T. elegansoides sp. nov., T. griseolus (Klug), T. incanus (Klug), T. lotus (Loew), T. obliteratus (Loew), and T. polyphemus (Wiedemann). Taxonomic comments, an identification key to species, diagnoses, and photographs of some species and genitalia are provided. Based on wing morphology and male genitalic characters, T. lotus clearly does not fit in the genus Thyridanthrax, and may need to be placed elsewhere, nevertheless it is not clear whether it can be included in any of the other currently recognized genera in the tribe Villini. It is here kept in Thyridanthrax until a more rigorous study can be conducted to better ascertain its position in the Villini.